2021
DOI: 10.47162/rjme.62.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of chemokine receptor in neuroendocrine neoplasms (CXCR4) of the gastrointestinal tract: a retrospective study of 71 cases

Abstract: Aim: C-X-C motif chemokine receptor 4 (CXCR4) is expressed in many tumor entities, including gastrointestinal neuroendocrine neoplasms (GI-NENs). However, the role of CXCR4 expression in GI-NENs has been less studied. Our objective was to investigate the expression of CXCR4 in a series of GI-NENs with various clinical and pathological features. Methods: The immunohistochemical (IHC) expression of CXCR4 (clone UMB2) was examined in 71 GI-NENs and a semiquantitative immunoreactivity score (IRS) was calculated ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…No clear agreement exists about the relationship between CXCR4 expression and GEP-NEN location. While Mai et al showed higher expression in those whose primary tumor is located in the appendix or colon (p = 0.024) [81], Popa et al showed no statistical differences among them, but greater expression in colonic primary tumors but less immunoreactive intensity in appendix ones [82]. Interestingly, no statistical differences were found in both studies between primary tumors and metastases in the intensity of expression.…”
Section: Implications Of Cxcr4 Expression In Nensmentioning
confidence: 93%
“…No clear agreement exists about the relationship between CXCR4 expression and GEP-NEN location. While Mai et al showed higher expression in those whose primary tumor is located in the appendix or colon (p = 0.024) [81], Popa et al showed no statistical differences among them, but greater expression in colonic primary tumors but less immunoreactive intensity in appendix ones [82]. Interestingly, no statistical differences were found in both studies between primary tumors and metastases in the intensity of expression.…”
Section: Implications Of Cxcr4 Expression In Nensmentioning
confidence: 93%
“…CXCR4 is associated with the occurrence, progression, invasion, and metastasis of a variety of malignant tumors according to previous literatures (12)(13)(14)(15)(16). CXCR4 has also been considered a prognostic factor in NENs, its expression level correlates with the malignancy of NENs (17,18). In a retrospective study, Popa et al found that high CXCR4 expression was associated with high-grade advanced NENs and tumor metastasis (18).…”
Section: Introductionmentioning
confidence: 91%
“…CXCR4 has also been considered a prognostic factor in NENs, its expression level correlates with the malignancy of NENs (17,18). In a retrospective study, Popa et al found that high CXCR4 expression was associated with high-grade advanced NENs and tumor metastasis (18).…”
Section: Introductionmentioning
confidence: 99%
“…Chemokyne receptor 4 is expressed in GI-NETs. Its immunohistochemical expression is related to grade 3 and metastatic disease and represents a proper target therapy by antagonists of this receptor[ 47 ].…”
Section: Diagnosismentioning
confidence: 99%